Hubungan Dukungan Suami dengan Penerimaan Diri Ibu yang Memiliki Anak Berkebutuhan Khusus - Kusumawardani, Nurul; Iftayani, Itsna (Journal of Psychosociopreneur, 2024)
This study aims to determine whether there is a relationship between husband's support and self-acceptance of mothers who have children with special needs. This study uses a quantitative method with a correlational research type. The population in this study was 170 mothers. In this study using accidental sampling technique with this technique can obtain a sample of 80 mothers who have children with special needs and this study uses correlation test analysis. In this study based on the results of the Spearman rho correlation test between husband's support and self-acceptance showed an r value of 0.864 with a p value of 0.000 (p <0.05). Based on this analysis there is a significant positive relationship between the two variables, namely husband's support and self-acceptance of mothers who have children with special needs. So in the study, husband's support is the main support factor for mother's self-acceptance.